A Single-Molecule Chemical Reaction Studied by High-Resolution Atomic Force Microscopy and Scanning Tunneling Microscopy Induced Light Emission - Kaiser, Katharina (ACS Nano, 2019)
[Image: see text] Atomic force microscopy (AFM) as well as scanning tunneling microscopy induced light emission (STM-LE) are, each on their own, powerful tools used to investigate a large variety of properties of single molecules adsorbed on a surface. However, accessing both structural information by AFM as well as optical information by STM-LE on the same molecule so far remains elusive. We present a combined high-resolution AFM and STM-LE study on single metal-oxide phthalocyanines. Using atomic manipulation, the molecules can be deliberately reduced. We demonstrate structure elucidation and adsorption geometry determination of single molecules with atomic resolution combined with optical characterization by STM-LE and the possibility of investigating the change in a molecule’s exciton emission intensity by a chemical reaction.